(untitled) (Journal of Hama University, 2026)
This Research Aims To Identify The Degree Of Acquisition Of Mathematics Concepts Among Children Of Third Category (5-6) Years, And Reveal The Differences Between Children In Degree Of Acquisition Of Mathematics Concepts Depending On The Gender, And Place Of Residence Variables. Follow The Descriptive Approach, And Used Mathematics Concepts Test Prepared By The Researcher As a Research Tool As, It Was Formed In Its Final Form Of (14) Items Formulated According To The Frair Model, The Test was applied To a sample Of (153) Children Of The Third Category In Latakia Governorate" The Results Showed That The Degree Of Acquisition Of Mathematics Concepts Among Children Of Third Category (5-6) Years Came Less Than Average "Weak"- There Is No Differences In Degree Of Acquisition Of Mathematics Concepts Among Children Of Third Category (5-6) Years According To Gender, And Place of Residence Variables.